Astrophysics of Shadows: The Dead Universe Theory - An Alternative Perspective on the Genesis of the Universe (Global Journal of Science Frontier Research, 2024)
This article presents the theory of the "dead universe" as a new perspective on the origin and evolution of the cosmos. It proposes that our universe may have emerged from remnants of a previous universe, vastly larger than the observable universe, which collapsed and perished, transforming into a defunct entity whose laws still influence our cosmos. Furthermore, the theory suggests a second hypothesis, in which this universe, from its very creation, has always been immersed in a state of death-not in the traditional sense of stellar death, but as a primordial existence characterized by the total absence of light. In this chaotic context, light, which was not an intrinsic quality of this universe, emerged as a cosmic anomaly, culminating in the formation of the observable universe, which now resides at the center of a black hole belonging to the dead universe.
Keywords: dead universe theory; cosmic heat death; universe's end; big freeze scenario